Application of Gene Classification in Cytogenetics - Huai Tang Gu (Journal La Lifesci, 2020)
Generality and individuality are the inherent nature of everything, everything has both generality and individuality. Generality determines the basic nature of things, and individuality reveals the differences between things. According to the principle of dialectical materialism, the genes of organisms are divided into two types: General genes and individual genes. Genes shared by all biological individuals are called general genes, and genes unique to each individual organism are called individual gene. And use this classification method to discuss the three basic laws of genetics, heterosis theory and mutual affinity, and population genetics and biological evolution. It is concluded three basic laws of genetics are only relative to individual genes, unit traits controlled by general genes are not restricted by three basic laws of genetics, and the proportion of individual gene and general gene between parents has a decisive influence on the mutual affinity of parents and heterosis of hybrid generation, and the gradual process of the evolution of life from simple to complex, from low-level to high-level, is achieved by that the mutations to generate firstly new individual genes, and then the favorable individual genes are generalized, which the individuality genes are transformed into general genes that the individual characters can be transformed into the common characteristics of the population, and the process of natural selection is just to fix the favorable individual genes, make the traits controlled by them change into the general characteristics of this population, and to eliminate the unfavorable genes, and eliminate the unfavorable traits..